2006
DOI: 10.1638/05-032.1
|View full text |Cite
|
Sign up to set email alerts
|

Cholelithiasis in Four Callitrichid Species (Leontopithecus, Callithrix)

Abstract: Medical records of three male and three female callitrichids of four species (Leontopithecus chrysopygus, Leontopithecus rosalia, Callithrix argentata argentata, Callithrix kuhlii) diagnosed with cholelithiasis were reviewed. Ages of affected animals at the time of diagnosis ranged from 2-14 yr. Definitive antemortem diagnosis of cholelithiasis was made in four of the six cases. Chronic weight loss, lethargy, and weakness were seen in all cases. Chronic intermittent diarrhea was seen in three cases. Icterus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 7 publications
1
25
1
Order By: Relevance
“…The effects of nutrition and illness on weight in these primates remains poorly understood [Kirkwood, 1983], though some recent progress has been made [Gozalo and Montoya, 1991;Smith et al, 2006]. Field studies of wild saddle-backed tamarins (Saguinus fuscicollis) have shown that weight may fluctuate in response to food availability [Goldizen et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of nutrition and illness on weight in these primates remains poorly understood [Kirkwood, 1983], though some recent progress has been made [Gozalo and Montoya, 1991;Smith et al, 2006]. Field studies of wild saddle-backed tamarins (Saguinus fuscicollis) have shown that weight may fluctuate in response to food availability [Goldizen et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Field studies of wild saddle-backed tamarins (Saguinus fuscicollis) have shown that weight may fluctuate in response to food availability [Goldizen et al, 1988]. In addition, tumors, gallstones, viral, bacterial and parasitic infections have been documented to cause weight loss [Baichman et al, 2006;Hawkins et al, 1997;Logan and Kahn, 1996;Ludlage and Mansfield, 2003;Pearson et al, 1987;Sainsbury et al, 1987;Smith et al, 2006]. Marmosets are susceptible to a number of chronic inflammatory colitis conditions [Sainsbury et al, 1993;Smith et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, spontaneous cholelithiasis has been reported in several species of primates (Anver et al, 1972;Baer et al, 1990;Pissinatti et al, 1992;Smith et al, 2006;Slingluff et al, 2010;Plesker et al, 2012;Lieberman et al, 2016). Although little is known about gallstones in AGMs, in some aspects the development of gallstones in humans and in susceptible species such as some Saimiri species (Lieberman et al, 2016) and AGMs share similarities.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, these historical model animals have been replaced by rodent models such as the Syrian hamster and mouse models (Combettes-Souverain et al, 2002;Wang and Lee, 2008). However, cholelithiasis and its associated disorders appear to be less common in primates compared to humans (Smith et al, 2006). To date, diet-induced cholesterol gallstones have been described in AGMs (Rudel et al, 1994, whereas little is known about spontaneous gallstones in AGMs, especially pigment and mixed gallstones.…”
Section: Introductionmentioning
confidence: 99%